1989
DOI: 10.1177/000841748905600304
|View full text |Cite
|
Sign up to set email alerts
|

Hand Splints and Cerebral Spasticity: A Review of the Literature

Abstract: The literature pertaining to the use of hand splints to treat cerebral spasticity is reviewed. Splinting patients with hand dysfunction as a result of spasticity remains a controversial treatment technique because of a paucity of research, methodological weakness in study designs, and contradictory results from investigations. The various splint designs commonly used. the corresponding neurophysiological rationale and research examining splinting and spasticity are discussed. Sug,gestions incorporating ,sound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The most commonly used splints fall into the categories of volar and dorsal splints, splints involving a finger spreader principle, and those using a cone (Langlois, MacKinnon & Pederson, 1989). Since they found no reduction in the EMG activity after the application of various splint designs, they concluded that there was not an immediate reduction of spasticity; however, they based this conclusion on the assumption that EMG alone can indicate spasticity.…”
Section: Splintingmentioning
confidence: 99%
“…The most commonly used splints fall into the categories of volar and dorsal splints, splints involving a finger spreader principle, and those using a cone (Langlois, MacKinnon & Pederson, 1989). Since they found no reduction in the EMG activity after the application of various splint designs, they concluded that there was not an immediate reduction of spasticity; however, they based this conclusion on the assumption that EMG alone can indicate spasticity.…”
Section: Splintingmentioning
confidence: 99%
“…Volar splint [14][15][16] The resting volar splint was one of the earliest splint designs which attempted to reduce spasticity by placing a muscle under constant stretch with increased tone. This excessive stretching of spastic muscles was thought to cause their muscle spindles to rebase so that they would become less sensitive to stretching.…”
Section: Splint Descriptionmentioning
confidence: 99%
“…This excessive stretching of spastic muscles was thought to cause their muscle spindles to rebase so that they would become less sensitive to stretching. 16 Dorsal splint 15,16 Using their rationale, a dorsal splint is expected to facilitate the forearm's extensor musculature by cutaneously stimulating the dorsal aspect and inhibiting the flexor muscles. 16 Finger spreader 16 The use of a foam finger spreader to cover the fingers and thumb is recommended; this role is suggested to encourage extensor muscles and to prevent flexor muscles.…”
Section: Splint Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical observations suggest that tone is reduced with splmts, experimental evidence is scarce and studies have not determined the most effective design (17)(18)(19). Additionally, whether static splmtmg can actually predispose to joint stiffenmg, muscle atrophy, and fixed joints positioning remams controversial (17,19). Orthoses control joint instability and may alter the loadmg of a limb to prevent stretch reflex activity m antagonist muscles.…”
Section: Physical Therapymentioning
confidence: 99%